The effect of Sauropus androgynus leaves extracted at different methods on performance and carcass quality in broiler chickens - Urip Santoso; Kususiyah Kususiyah; Suharyanto Suharyanto (Faculty of Animal Science, Universitas Brawijaya, 2022)
The objective of this study was to analyze the effect of Sauropus androgynus leaves extracted at different methods on performance and carcass quality in broiler chickens. One hundred and eighty broilers aged 20 days were divided into six groups as follows: Broilers were fed a diet containing 5 g commercial feed supplement /kg as the control (P0); Broilers were fed a diet containing 2.5 g commercial feed supplement /kg plus 2.5 g Sauropus androgynus leaf (SAL) extracted at a 90oC/kg (P1); Broilers were fed diet containing 5 g SAL extracted at a 5°C/kg (P2); Broilers were fed diet containing 5 g SAL extracted at a 30°C/kg (P3); Broilers were fed diet containing 5 g SAL extracted at a 60oC/kg (P4); Broilers were fed diet containing 5 g SAL extracted at a 90°C/kg (P5). Sauropus androgynus leaves extracted at different methods significantly (P<0.05) affected body weight, and cholesterol, protein, vitamin E, and β-carotene contents of meats (p<0.05), but it did not significantly affect feed intake, feed conversion ratio, carcass weight, carcass color cooking loss, meat taste and odor, and meat fat contents (P>0.05). In conclusion, supplementation of Sauropus androgynus extracted at 30oC could replace 100% commercial feed supplement. Supplementation of Sauropus androgynus leaf extracted at 60oC or 90°C reduced meat cholesterol. In addition, this extract inclusion resulted in higher meat protein content as compared with the control.